'Najm' and 'Shadīdu'l-quwā' in Sūrat al-Najm: A Cross-Textual Analysis of the Prophet's Ascension - Shabani, Azam Sadat (Studies in interreligious dialogue, 2025)
According to some Islamic commentators, Sūrat al-Najm (Q53), together with Sūrat al-Isra (Q17), addresses the Prophet’s ascension. By analyzing the opening verses of Q53 and delving into the pre-Qur’anic understanding of the Prophet’s ascension, we can reconstruct an interpretation that challenges traditional views. Different interpretations of 'Najm' and 'Shadīdu’l-quwā' have contributed to a contentious perception of the ascension in Q53. This article presents a fresh perspective on the concept of 'Najm' in relation to ascension, utilizing logical inference for clearer understanding. An examination of both internal and external religious discourses supports this viewpoint. Moreover, aligning the concept of 'Najm' with the Holy Bible, considering its symbolism in pre-Qur’anic times, and emphasizing rationality in understanding shed light on the ascension. The aim of this research is to propose a possible interpretation of these terms in relation to the concept of ascension, alongside established commentaries using the Holy Bible.